A Mild and Regiospecific Synthesis of Pyrazoleboranes. Issue 22 (29th March 2017) - Brown, Andrew W.; Comas‐Barceló, Júlia; Harrity, Joseph P. A.
Abstract: Alkynylboranes show unprecedented reactivity in their [4+2] cycloaddition of sydnones offering access to fully substituted pyrazoles within a few hours at room temperature. This method delivers synthetically valuable pyrazoleboranes with complete control of regioselectivity, and these intermediates can be further elaborated through functionalization of the C−B bond. Abstract : Go direct ! Alkynylboranes show unprecedented reactivity in their [4+2] cycloaddition of sydnones offering access to fully substituted pyrazoles within a few hours at room temperature. This method delivers synthetically valuable pyrazoleboranes with complete control of regioselectivity, and these intermediates can be further elaborated through functionalization of the C−B bond.